SOCIO-ECONOMIC ESSENCE OF ORGANIZING DIGITAL MARKETING ACTIVITY IN INDUSTRIAL ENTERPRISES (Marketing Journal, 2025)
This article reveals the specifics of organizing digital marketing activities in industrial enterprises. The importance of digital marketing for industrial sectors, its impact on economic growth and its differentiation according to social characteristics are discussed. The article covers issues such as increasing the competitiveness of industrial enterprises in the market through digital technologies, brand development and expanding access to the global market. It also examines the social and economic consequences of digital marketing, including its impact on the labor market and the development of human capital.
Keywords: digital marketing; industrial enterprises; socio -economic development; technologies; brand development; competitiveness; labor market; human 219 capital